Determination of Vitamins D2 and D3 in Edible Fungus by Reversed-Phase Two-Dimensional Liquid Chromatography - Bai-Fen Huang; Xiao-Dong Pan; Jing-Shun Zhang; Jiao-Jiao Xu; Zeng-Xuan Cai (Journal of Food Quality)
Vitamin D is the name given to a series of compounds with antirachitic activity. In this study, we developed a method for quantification of the common Vitamin D, ergocalciferol (vitamin D2), and cholecalciferol (vitamin D3), in edible fungus by reversed-phase two-dimensional liquid chromatography. The sample was saponified by KOH ethanol solution and extracted with ethyl acetate and n-hexane. After reconcentration, the sample was directly injected for instrumental analysis. The results showed that the spiking recoveries of vitamin D2 and vitamin D3 were 80.4–93.8% and 82.3–92.0%, respectively. The relative standard deviations (RSDs) were all less than 5%. Comparing to the results of isotope dilution liquid chromatography tandem mass spectrometry, there were no significant differences (P>0.05). The method was applied for testing vitamin D2 and D3 in 9 kinds of edible mushrooms. It showed that vitamin D3 was not detected. The content of vitamin D2 ranged from 0.11 μg/100 g to 123 μg/100 g. The content of vitamin D2 in dried mushroom was the highest, while that in fresh mushroom was the lowest. The limit of quantification was 0.025 μg/100 g.